Perbedaan Produksi dan Pendapatan Petani Padi Sawah antara yang Mengadopsi Teknologi Tanam Benih Langsung dan Tanam Pindah di Desa Puuroda Kecamatan Baula Kabupaten Kolaka - Paembonan, Fransilia; Rianse, Usman; Abdullah, Weka Gusmiarty (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study aims to determine: (1) differences in the production of lowland rice farmers between those who adopted direct seed planting and transplanting technology in Puuroda Village, Baula Subdistrict, Kolaka Regency and (2) The gap in income between lowland rice farmers who adopted direct seed planting technology and transplanting in Puuroda Village, Baula District, Kolaka Regency. This research was conducted in Puuroda Village, Baula District, Kolaka Regency with a total sample of 72 respondents. Data collection techniques in this study are observation methods carried out by direct observation of the rice farming activities that are the object of research. Structured interview methods using questionnaires and direct observations in the field are used as primary data collection techniques. Librarian recording or study techniques are used as secondary data collection techniques. Secondary data were obtained from the Central Bureau of Statistics, the office of the Puuroda Village, as well as the results of previous studies that supported data analysis. Data analysis used in this study was an analysis of different test of production and income and Gini Ratio Index. The results of the study showed that (1) the production and income of wetland rice using Tabela technology and Tapin technology were significantly different, where the production and revenue of Tabela technology were higher than that of Tapin technology. (2) The level of the income gap between lowland rice farmers who adopt Tabela and Tapin technology was at moderate levels of inequality.